Engaging Youth in Civic Participation - Riley, Shelly-Ann (My University, 2006)
This research explored the question of 'how to engage youth in civic participation?' This study was necessary because youth as a vulnerable population are often marginalized and excluded from meaningful participation in society. Civic participation is defined and addressed in varying ways in the literature. The exploration into the topic of civic participation in this research is important as to directly involve the youth and give space for them to explore and express their own definitions and conceptions of civic participation, as well as major obstacles preventing them from participating. This study attempted to explore the complexity of youth participation. What are the youth really interested in? What prevents them from participating? What are their concerns? Semi-structured in-depth interviews were conducted in order for the researcher to delve into the difficulties and experiences of the youth participants in civic participation.
This report provides a summary of the existing literature on engaging youth in civic participation. In the findings and discussion section I will highlight two major aspects for critical examination. The first is the discourse on youth civic participation, which included, definition of youth civic participation; how does youth participate; the meaning attached to youth; and how to engage youth? The second issue is the discrepancies between the existing understanding of the barriers to youth civic participation in society. This study points to the fact that a common, or widely acceptable definition of civic participation does not exist in the academic literature or other forms of literature. The findings also suggest that existing definitions tend to be elitist and do not reflect the everyday lived experiences and realities of youth and their community involvement. The report then emphasizes three critical implications for social work research. First, in-depth interviews should be used more often in conducting research on youth civic participation so that they could share their experience and ideas in less restrictive ways. Second, the present elitist definitions of civic participation should not be imposed on youth. Last but not least, youths' definitions of community should be included in the conversations on civic participation.
Keywords: Social Work; Social Work